2020
DOI: 10.1053/j.gastro.2020.07.039
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide Orodispersible Tablets Maintain Remission in a Randomized, Placebo-Controlled Trial of Patients With Eosinophilic Esophagitis

Abstract: up to 48 weeks. RESULTS: At end of treatment, 73.5% of patients receiving BOT 0.5 mg twice daily and 75% receiving BOT 1.0 mg twice daily were in persistent remission compared with 4.4% of patients in the placebo group (P < .001 for both comparisons of BOT with placebo). Median time to relapse in the placebo group was 87 days. The frequency of adverse events was similar in the BOT and placebo groups. Morning serum levels of cortisol were in the normal range at baseline and did not significantly change during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
25

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 113 publications
(128 citation statements)
references
References 35 publications
3
100
0
25
Order By: Relevance
“…Neither is it consistent with Table 1 where the symptom scores after PPI maintenance were 0‐4 in 8.3% and 5‐15 in 92%. The latter would be even lower than the placebo response rates observed in recent randomised controlled trials of budesonide for induction and maintenance 7,8 …”
mentioning
confidence: 75%
“…Neither is it consistent with Table 1 where the symptom scores after PPI maintenance were 0‐4 in 8.3% and 5‐15 in 92%. The latter would be even lower than the placebo response rates observed in recent randomised controlled trials of budesonide for induction and maintenance 7,8 …”
mentioning
confidence: 75%
“…Since EoE is a chronic disease and relapses occur rapidly after cessation of an induction treatment, a maintenance therapy is required. Subsequently, two controlled long-term studies using budesonide have demonstrated that this compound is able to maintain a clinico-histological remission in up to 75% of the patients, whereas less than 5% of the participants under placebo were still in remission after one year of treatment [ 67 ]. Of note, as four of the total 136 patients (≈3 % ) exposed to budesonide had decreased morning cortisol levels, further studies evaluating the safety of the long-term use of STCs are needed.…”
Section: Typical Clinical Presentation Diagnosis and Treatment Of Eosinophilic Esophagitismentioning
confidence: 99%
“…However, the six-food elimination diet significantly impacts life quality, limiting the compliance for this treatment for EoE [130][131][132]. Topical corticosteroids improve clinical symptoms and are highly efficacious for induction and maintenance therapy of EoE [133,134]. Small molecules and biologicals that specifically target checkpoints are of significant interest to further improve the treatment of EoE.…”
Section: Eosinophilic Esophagitismentioning
confidence: 99%